(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article deals with the educational conditions for the formation of special competence of the future agricultural engineering specialists in the process of professionally oriented training in physics. The authors analyse approaches to integrating physical knowledge with professional tasks, relevant to the branch of agricultural engineering, emphasizing the importance to develop in the students a comprehensive understanding of the relationship between the theoretical foundations and the solutions of practical engineering. There is revealed the importance of an interdisciplinary approach in creating educational programs, aimed at the development of the students' ability to apply physical laws and principles in order to solve real problems of production. There are identified the key educational conditions that contribute to the formation of special competence, including: application of problem-oriented learning, aimed at the development of the students' skills in independent analysis of engineering problems and finding solutions; the use of modern technologies for modelling physical processes, allowing for the visualization of complex phenomena and the reproduction of working scenarios of the agricultural engineering activities; the development of critical thinking, ensuring the ability to evaluate and interpret scientific data in a professional context; the formation of teamwork skills, which is important for efficient interaction in production conditions and solution of complex problems. Particular attention is paid to the digital educational technologies, such as virtual laboratories, digital simulators and software packages that simulate technological processes in the agricultural sector. These tools allow the students to practice engineering skills, to test various models, and analyse their efficiency without the risk of real losses. An impact is assessed in the study of these educational conditions upon the level of training the students in the field of agricultural engineering. The results showed that the use of an integrative approach and digital technologies helps to raise the level of mastery of the educational material by 30–35%, to increase the degree of the students’ involvement in the educational process, and develop practical engineering skills. Analysis of academic performance has shown that the students studying in a digital and practice-oriented educational environment are by 40% better at the tasks that require an analytical approach and by 25% faster at adaptation to professional conditions. A conclusion is made that the creation of favourable educational conditions, based on a combination of traditional and innovative teaching methods, can improve the efficiency of professional training of agricultural engineers, ensuring their readiness to solve complex engineering problems, develop innovative thinking and successfully adapt to digital transformations in the agro-industrial complex.